2000
DOI: 10.1001/archsurg.135.11.1265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Steroids and Retinoids on Wound Healing

Abstract: Anti-inflammatory corticosteroids significantly impair wound healing. Retinoids partially, but significantly, reverse this effect. Little is known about the mechanism of steroid retardation or retinoid reversal. We hypothesized that corticosteroids lower transforming growth factor-␤ (TGF-␤) and insulinlike growth factor-I (IGF-I) levels and tissue deposition in wounds and that retinoids stimulate corticosteroid-impaired TGF-␤ and IGF-I release and collagen production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
177
0
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(204 citation statements)
references
References 28 publications
(27 reference statements)
7
177
0
10
Order By: Relevance
“…A prior case series of corticosteroid users undergoing THA showed postoperative complications requiring reoperation included periprosthetic fracture, recurrent hip dislocation, and persistent deep infection [20]. Potential mechanisms for the association between corticosteroids and revision include poor bone formation secondary to suppression of osteoblasts [7], poor bone stock increasing the risk for fracture and prosthesis loosening [7], inhibition of collagen deposition and secretion of growth factors leading to impaired wound healing [27], and weakened immune function leading to infection [1,17]. In a future study, long-term followup of chronic corticosteroid users at 5-year and 10-year endpoints would be useful to comprehensively assess implant survival in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…A prior case series of corticosteroid users undergoing THA showed postoperative complications requiring reoperation included periprosthetic fracture, recurrent hip dislocation, and persistent deep infection [20]. Potential mechanisms for the association between corticosteroids and revision include poor bone formation secondary to suppression of osteoblasts [7], poor bone stock increasing the risk for fracture and prosthesis loosening [7], inhibition of collagen deposition and secretion of growth factors leading to impaired wound healing [27], and weakened immune function leading to infection [1,17]. In a future study, long-term followup of chronic corticosteroid users at 5-year and 10-year endpoints would be useful to comprehensively assess implant survival in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Skin that has become atrophic as a consequence of the aging process also demonstrates impaired wound healing, 5-7 as does skin that has been damaged as a result of extended corticosteroid use. [8][9][10] The majority of wound-healing research is directed toward understanding the pathophysiology of impaired wound healing and identifying interventions that can mitigate the critical patho-physiological events.Several past studies have demonstrated the efficacy of all-trans retinoic acid (RA) and its parent compound all-trans retinol (ROL, vitamin A) in wound healing. Although most studies have focused on wounds in the skin, [11][12][13][14][15][16][17] retinoid efficacy has also been demonstrated in healing of wounds in other tissues (bone, cornea, respiratory tract, upper digestive system, and gut).…”
mentioning
confidence: 99%
“…This study demonstrates that the cht/soy membranes, in a rodent model under impaired healing conditions induced by corticosteroid treatment, 49 are suitable wound dressings, allowing the progress of a normal healing path and a faster replacement of the excised epidermis in comparison to an undressed wound (negative control). The presence of granulation tissue at earlier stages of healing was indicative of an accelerated tissue reaction 55 toward the repair of the injured site.…”
Section: Discussionmentioning
confidence: 76%
“…1). At days 0 (surgery day) and 7, methylprednisolone acetate (Depo-Medrol Ò ; Pfizer) was subcutaneously injected (20 mg/kg BW) to impair wound healing 49 and inhibit hair growth.…”
Section: Animalsmentioning
confidence: 99%